Salt core, injection molding product, preparation method of injection molding product and water outlet device shell

By adopting water-soluble salt core, the problems of insufficient strength and low discharge efficiency in metal powder injection molding faucets are solved, and the salt core with high mechanical strength and toughness is achieved. It is suitable for the production of irregularly shaped faucets, which improves the Product hot water decoding efficiency.

CN119282117AActive Publication Date: 2025-01-10JOMOO KITCHEN & BATHROOM
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411280032.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-24
Filing Date
2024-09-12
Publication Date
2025-01-10
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The medium core of traditional metal powder injection molding faucets has insufficient strength, poor thermal stability, low discharge efficiency and environmental protection problems, making it difficult to produce irregular special-shaped faucets.

Method used

A water-soluble salt core, including sodium chloride, magnesium oxide, diatomaceous earth, water glass, polyvinyl alcohol fibers and binders, is prepared by drying, pressing and sintering to form a salt core with high mechanical strength and toughness. , used for hot water decoding process for metal powder injection molding products.

Benefits of technology

It realizes that the water-soluble salt core is not easy to block the powder flow channel at high temperatures, improves the strength and decore efficiency of the faucet, and is suitable for the production of irregularly shaped metal powder injection molding products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a salt core and a preparation method thereof, an injection molding product and a preparation method thereof, and a water outlet device shell. The water-soluble salt core comprises the following components in percentage by mass: 50%-60% of sodium chloride, 5%-15% of magnesium oxide, 5%-10% of diatomite, 5%-15% of water glass, 3%-10% of polyvinyl alcohol fiber and 3%-10% of a binder. The water-soluble salt core has high mechanical strength and toughness, has good hydrolysis collapsibility, and facilitates implementation of a hot water depoling process when a metal powder injection molding product is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of home and life technology, and in particular to a water-soluble salt core and a preparation method thereof, a metal powder injection molding product and a preparation method thereof, and a water outlet device housing. Background Art

[0002] When metal powder injection molding faucets are used, the core pulling mechanism can only perform straight core pulling or regular curvature curve core pulling, so the existing core pulling mechanism cannot produce irregular shaped faucets. In order to realize the use of metal powder injection molding process to prepare special-shaped faucets, it is key to obtain a core that is easy to be removed. In traditional technology, there are mainly the following technical solutions: using a resin core made of POM (polyoxymethylene) + PVA (polyvinyl alcohol) material, when the mold temperature rises to 120°C during the injection molding of the faucet, the resin core will block the flow channel of the powder due to thermal expansion, resulting in product shortage; using an aluminum alloy material aluminum core injection molding faucet, during the process of using sodium hydroxide to remove the core, it is easy to produce hydrogen and gather in the inner cavity of the faucet, resulting in the faucet blank not being sintered at high temperature, low strength, and cracking. In addition, the aluminum core has problems such as low removal efficiency and the use of sodium hydroxide is not environmentally friendly. Using conventional salt cores, there is a problem that the salt core is not strong enough, and the salt core is prone to breakage or even crushing during the metal powder injection molding process of faucets. Summary of the invention

[0003] Based on this, it is necessary to provide a water-soluble salt core. The water-soluble salt core of the present invention has high mechanical strength and toughness, good hydrolysis and disintegration performance, and is helpful for the hot water core removal process when preparing metal powder injection molding products.

[0004] An embodiment of the present application provides a water-soluble salt core.

[0005] A water-soluble salt core comprises the following components in percentage by mass: 50% to 60% sodium chloride, 5% to 15% magnesium oxide, 5% to 10% diatomaceous earth, 5% to 15% water glass, 3% to 10% polyvinyl alcohol fiber, and 3% to 10% binder.

[0006] In some of the embodiments, the following components are included in mass percentage: 50% to 60% sodium chloride, 7.5% to 12.5% ​​magnesium oxide, 5% to 8% diatomaceous earth, 5% to 12.5% ​​water glass, 3% to 7.5% polyvinyl alcohol fiber, and 5% to 10% binder.

[0007] In some of the embodiments, the following components are included in weight percentage: 55% to 60% sodium chloride, 7.5% to 10% magnesium oxide, 7% to 7.5% diatomaceous earth, 7.5% to 12.5% ​​water glass, 5% to 7.5% polyvinyl alcohol fiber, and 5% to 7.5% binder.

[0008] In some embodiments, the binder includes silica sol.

[0009] In some of the embodiments, the water-soluble salt core has a withstand pressure greater than 150 MPa, and the water-soluble salt core can be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70° C. to 100° C. for 30 min to 120 min.

[0010] An embodiment of the present application also provides a method for preparing a water-soluble salt core.

[0011] A method for preparing the water-soluble salt core comprises the following steps:

[0012] Drying the sodium chloride, magnesium oxide and diatomaceous earth respectively;

[0013] The dried sodium chloride, magnesium oxide, diatomaceous earth, water glass, polyvinyl alcohol fiber and binder are mixed evenly according to a preset ratio to obtain a mixed material;

[0014] placing the mixed material in a salt core mold for compression processing to obtain a compressed intermediate; and

[0015] The pressed intermediate is sintered to obtain a water-soluble salt core.

[0016] In some of the embodiments, during the drying process, the drying temperature is 150° C. to 200° C., and the insulation time is at least 3 hours.

[0017] In some of the embodiments, during the pressing process, the temperature of the salt core mold is controlled to be 80° C. to 120° C., the pressing pressure is 200 MPa to 300 MPa, and the pressing time is 3 min to 10 min.

[0018] In some of the embodiments, during the sintering process, the sintering temperature is 200° C. to 250° C., and the holding time is 0.5 h to 2 h.

[0019] In some embodiments, after the drying process, at least one of the following conditions is met:

[0020] (1) Controlling the particle size of the sodium chloride to be 50 μm to 100 μm;

[0021] (2) Controlling the particle size of the magnesium oxide to be 50 μm to 100 μm;

[0022] (3) The particle size of the diatomaceous earth is controlled to be 50 μm to 100 μm.

[0023] In some of the embodiments, when the mixed material is placed in a salt core mold for pressing, the following step is also included: pressurized CO2 is introduced into the salt core mold, wherein the pressure of CO2 is 0.5Mpa~1Mpa.

[0024] An embodiment of the present application also provides a water-soluble salt core.

[0025] An embodiment of the present application also provides a method for preparing a metal powder injection molding product.

[0026] A method for preparing a metal powder injection molding product comprises the following steps:

[0027] Placing a water-soluble salt core in a mold cavity of a molding die, wherein a gap between the water-soluble salt core and the mold cavity of the molding die forms a molding chamber;

[0028] Placing metal powder in a molding cavity between the water-soluble salt core and the molding cavity of the molding mold for injection molding; and

[0029] The molding mold is removed, and the water-soluble salt core and the injection product are immersed in hot water at a temperature of 70° C. to 100° C. for 30 min to 120 min to hydrolyze and disintegrate the water-soluble salt core to obtain a metal powder injection molding product.

[0030] In some of the embodiments, during injection molding, the molding pressure is 150 MPa to 200 MPa.

[0031] In some embodiments, the metal powder includes one or more of stainless steel powder, low alloy steel powder, titanium alloy powder and cemented carbide powder.

[0032] An embodiment of the present application also provides a water outlet device housing.

[0033] A water outlet device shell is prepared by adopting the preparation method of the metal powder injection molding product.

[0034] The water-soluble salt core has high mechanical strength and toughness, and has good hydrolysis and disintegration properties, which is helpful for implementing the hot water core removal process when preparing metal powder injection molding products. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0036] In the description of the present invention, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0037] In this article, unless otherwise stated, each reaction step may be carried out in the order described herein or may not be carried out in the order described herein. For example, other steps may be included between each reaction step, and the order of the reaction steps may also be appropriately swapped. This can be determined by the technician based on common knowledge and experience. Preferably, the reaction method herein is carried out sequentially.

[0038] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0040] The embodiment of the present application provides a water-soluble salt core to solve at least one of the following problems in the core used for the special-shaped faucet molded by metal powder injection molding in the traditional technology: the ordinary salt core is not strong enough, and the salt core is prone to breakage or even crushing; the resin core has poor thermal stability, and the thermal expansion will block the flow channel of the powder, resulting in product shortage; the aluminum core is not easy to come out, which is easy to cause the faucet blank to crack. The water-soluble salt core of the present application can be used for the purpose of special-shaped faucets molded by metal powder injection molding.

[0041] Exemplarily, a water-soluble salt core includes the following components in mass percentage: 50% to 60% sodium chloride, 5% to 15% magnesium oxide, 5% to 10% diatomaceous earth, 5% to 15% water glass, 3% to 10% polyvinyl alcohol fiber, and 3% to 10% binder.

[0042] In some of the embodiments, the following components are included in mass percentage: 50% to 60% sodium chloride, 7.5% to 12.5% ​​magnesium oxide, 5% to 8% diatomaceous earth, 5% to 12.5% ​​water glass, 3% to 7.5% polyvinyl alcohol fiber, and 5% to 10% binder.

[0043] In some of the embodiments, the following components are included in weight percentage: 55% to 60% sodium chloride, 7.5% to 10% magnesium oxide, 7% to 7.5% diatomaceous earth, 7.5% to 12.5% ​​water glass, 5% to 7.5% polyvinyl alcohol fiber, and 5% to 7.5% binder.

[0044] In some of the embodiments, the water-soluble salt core has a withstand pressure greater than 150 MPa, and the water-soluble salt core can be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70° C. to 100° C. for 30 min to 120 min.

[0045] The above-mentioned water-soluble salt core has high mechanical strength and toughness, and has good hydrolysis and disintegration properties, which is helpful for the hot water core removal process when preparing metal powder injection molding products. It should be noted that the above-mentioned hydrolysis and disintegration properties refer to the water-soluble salt core being able to disintegrate under water-soluble conditions at a temperature of 70°C to 100°C, and having excellent water-soluble and disintegration properties. Specifically, the diatomaceous earth used in this application has a porous characteristic. During the processing and pressing process of the water-soluble salt core preparation, it is easy to connect particles such as sodium chloride and magnesium oxide, thereby forming a large number of three-dimensional through-holes, thereby improving the strength and toughness of the water-soluble salt core. Polyvinyl alcohol fiber (PVA) has high strength, good affinity and binding properties with sodium chloride and magnesium oxide, which can improve the mechanical strength of the water-soluble salt core. At the same time, polyvinyl alcohol fiber (PVA) has good water solubility, which is helpful for the water-soluble salt core in the metal powder injection molding product preparation process to be de-cored by hot water. In addition, the present application has a multiple binder system, including a binder and water glass, which has a strong bonding strength and, together with the water glass, improves the mechanical strength of the water-soluble salt core.

[0046] In some embodiments, the binder includes silica sol. The present application uses silica sol as a binder, and silica sol has a strong bonding strength, and together with water glass, it improves the mechanical strength of the water-soluble salt core.

[0047] An embodiment of the present application also provides a method for preparing a water-soluble salt core.

[0048] A method for preparing a water-soluble salt core comprises the following steps:

[0049] S1. Drying sodium chloride, magnesium oxide and diatomaceous earth respectively.

[0050] S2. Evenly mix the dried sodium chloride, magnesium oxide, diatomaceous earth, water glass, polyvinyl alcohol fiber, and binder according to a preset ratio to obtain a mixed material.

[0051] S3, placing the mixed material in a salt core mold for compression processing to obtain a compressed intermediate.

[0052] S4. Sintering the pressed intermediate to obtain a water-soluble salt core.

[0053] In some embodiments, during the drying process, the drying temperature is 150°C to 200°C, and the holding time is at least 3 hours. The drying temperature includes but is not limited to: 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or a range between any two of the foregoing.

[0054] In some embodiments, during the pressing process, the salt core mold temperature is controlled to be 80°C to 120°C, the pressing pressure is 200Mpa to 300Mpa, and the pressing time is 3min to 10min. The salt core mold temperature includes but is not limited to: 80°C, 90°C, 100°C, 110°C, 120°C or a range between any two of the foregoing. The pressing pressure includes but is not limited to: 200Mpa, 210Mpa, 220Mpa, 230Mpa, 240Mpa, 250Mpa, 260Mpa, 270Mpa, 280Mpa, 290Mpa, 300Mpa or a range between any two of the foregoing. The pressing time includes but is not limited to: 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min or a range between any two of the foregoing.

[0055] In some embodiments, during the sintering process, the sintering temperature is 200°C to 250°C, and the holding time is 0.5h to 2h. The sintering temperature includes but is not limited to: 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, or a range between any two of the foregoing. The holding time includes but is not limited to: 0.5h, 1h, 1.5h, 2h, or a range between any two of the foregoing.

[0056] In some embodiments, after the drying process, at least one of the following conditions is met:

[0057] (1) Control the particle size of sodium chloride to 50 μm~100 μm;

[0058] (2) Control the particle size of magnesium oxide to 50 μm~100 μm;

[0059] (3) Control the particle size of diatomaceous earth to 50μm~100μm.

[0060] For example, in a specific embodiment, the particle size of sodium chloride includes but is not limited to: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range between any two of the foregoing.

[0061] For example, in a specific embodiment, the particle size of magnesium oxide includes but is not limited to: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range between any two of the foregoing.

[0062] For example, in a specific embodiment, the particle size of diatomaceous earth includes but is not limited to: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range between any two of the foregoing.

[0063] In some embodiments, when the mixed material is placed in a salt core mold for a pressing process, the following steps are also included: pressurized CO2 is introduced into the salt core mold, wherein the pressure of CO2 is 0.5Mpa~1Mpa. In the process of preparing a water-soluble salt core, the present application simultaneously introduces CO2 into the salt core mold during the pressing process. The CO2 with a certain positive pressure can make the water glass harden quickly, so that the prepared water-soluble salt core has a higher mechanical strength, and is also convenient for demolding the salt core mold. The pressure value of CO2 includes but is not limited to: 0.5Mpa, 0.6Mpa, 0.7Mpa, 0.8Mpa, 0.9Mpa, 1Mpa or a range between any two of the foregoing.

[0064] An embodiment of the present application also provides a water-soluble salt core.

[0065] A water-soluble salt core is prepared by the preparation method of the water-soluble salt core. The water-soluble salt core has a pressure tolerance greater than 150 MPa, and the water-soluble salt core can be hydrolyzed and dispersed after being soaked in hot water at a temperature of 70°C to 100°C for 30min to 120min.

[0066] An embodiment of the present application also provides a method for preparing a metal powder injection molding product.

[0067] A method for preparing a metal powder injection molding product comprises the following steps:

[0068] S1. placing a water-soluble salt core in a mold cavity of a molding mold, and a gap between the water-soluble salt core and the mold cavity of the molding mold forms a molding chamber.

[0069] S2. Placing metal powder in a molding chamber between the water-soluble salt core and the mold cavity of a molding mold for injection molding.

[0070] S3. Remove the molding mold, soak the water-soluble salt core and the injection product in hot water at a temperature of 70°C to 100°C for 30min to 120min to hydrolyze and disintegrate the water-soluble salt core to obtain a metal powder injection molding product.

[0071] In some embodiments, in step S2, the injection molding process includes the following steps: adding metal powder to a binder, stirring and mixing to obtain a mixture; injecting the mixture into the above-mentioned molding chamber through an injection machine, and pressing and molding at a temperature of 120°C to 150°C to obtain an injection product. The mass ratio of metal powder to binder is (60~70): (30~40), and the binder includes one or more of paraffin, polyethylene, polystyrene, polyoxymethylene, polypropylene, stearic acid, epoxy resin and phenolic resin.

[0072] In some embodiments, in step S3, after obtaining the metal powder injection molded product, the metal powder injection molded product is subjected to nitric acid degreasing and vacuum thermal degreasing in a vacuum furnace in a nitric acid atmosphere to remove the binder, and then sintered at 1200°C-1500°C for at least 30 hours after degreasing to improve its structural strength. The degreasing reaction includes nitric acid degreasing and vacuum thermal degreasing in sequence, and the degreasing process of vacuum thermal degreasing is to react at 150°C-160°C for at least 10 hours. The degreasing reaction and sintering are carried out in the same vacuum furnace.

[0073] In some embodiments, during injection molding, the molding pressure is 150 MPa to 200 MPa. The molding pressure includes but is not limited to: 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa or a range between any two of the foregoing.

[0074] In some embodiments, the metal powder includes one or more of stainless steel powder, low alloy steel powder, titanium alloy powder and cemented carbide powder. The specific type of metal powder can be selected according to the product to be prepared. Among them, cemented carbide powder is an alloy material made of a hard compound of a refractory metal and a bonding metal through a powder metallurgy process. The hard compound of the refractory metal includes tungsten carbide (WC), titanium carbide (TiC), tantalum carbide (TaC), etc., and the bonding metal includes cobalt, nickel, etc. For example, the cemented carbide powder can be tungsten steel powder, etc.

[0075] An embodiment of the present application also provides a water outlet device housing.

[0076] A water outlet device shell is prepared by adopting the above-mentioned method for preparing a metal powder injection molding product.

[0077] The water outlet device shell of the present application adopts the above-mentioned water-soluble salt core, which can realize the production of irregular water outlet device shells and is easy to demould in the production process.

[0078] In some of the embodiments, the water outlet device housing includes special-shaped faucets, water pipes and other equipment.

[0079] Example 1

[0080] This embodiment provides a water-soluble salt core.

[0081] The water-soluble salt core comprises the following components in percentage by mass: 50% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 15% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0082] The preparation method of the water-soluble salt core comprises the following steps:

[0083] S1. Dry the sodium chloride, magnesium oxide and diatomaceous earth separately at a drying temperature of 200°C and a heat preservation time of 3 hours.

[0084] S2. Mix the dried sodium chloride, magnesium oxide, diatomaceous earth with water glass, polyvinyl alcohol fiber and binder in the above preset proportions to obtain a mixed material, wherein sodium chloride with a particle size of 50 μm to 55 μm, magnesium oxide with a particle size of 50 μm to 55 μm, and diatomaceous earth with a particle size of 50 μm to 55 μm are selected.

[0085] S3. Place the mixed material in a salt core mold, introduce pressurized CO2 into the salt core mold, wherein the pressure of CO2 is 0.5 MPa, and perform pressing treatment to obtain a pressed intermediate. During the pressing treatment, the temperature of the salt core mold is controlled to 80°C, the pressing pressure is 300 MPa, and the pressing time is 3 min.

[0086] S4, sintering the pressed intermediate to obtain a water-soluble salt core. During the sintering process, the sintering temperature is 200° C. and the heat preservation time is 2 hours.

[0087] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 190 MPa and a tensile strength of 25 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being soaked in hot water at a temperature of 70°C to 100°C for 100 minutes.

[0088] Example 2

[0089] This embodiment provides a water-soluble salt core.

[0090] The water-soluble salt core comprises the following components in percentage by mass: 60% sodium chloride, 10% magnesium oxide, 5% diatomaceous earth, 5% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0091] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0092] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 155 MPa and a tensile strength of 18 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 30 minutes.

[0093] Example 3

[0094] This embodiment provides a water-soluble salt core.

[0095] The water-soluble salt core comprises the following components in percentage by mass: 60% sodium chloride, 15% magnesium oxide, 9% diatomaceous earth, 10% water glass, 3% polyvinyl alcohol fiber, and 3% binder, wherein the binder is silica sol.

[0096] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0097] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 170 MPa and a tensile strength of 21 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 50 minutes.

[0098] Example 4

[0099] This embodiment provides a water-soluble salt core.

[0100] The water-soluble salt core comprises the following components in percentage by mass: 55% sodium chloride, 12% magnesium oxide, 8% diatomaceous earth, 12.5% ​​water glass, 7.5% polyvinyl alcohol fiber, and 5% binder, wherein the binder is silica sol.

[0101] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0102] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 175 MPa and a tensile strength of 22 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 80 minutes.

[0103] Example 5

[0104] This embodiment provides a water-soluble salt core.

[0105] The water-soluble salt core comprises the following components in mass percentage: 57.5% sodium chloride, 7.5% magnesium oxide, 7.5% diatomaceous earth, 12.5% ​​water glass, 7.5% polyvinyl alcohol fiber, and 7.5% binder, wherein the binder is silica sol.

[0106] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0107] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 160 MPa and a tensile strength of 20 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 70 minutes.

[0108] Example 6

[0109] This embodiment provides a water-soluble salt core.

[0110] The mass percentage components of the water-soluble salt core are the same as those in Example 1.

[0111] The preparation method of the water-soluble salt core is basically the same as that of Example 1, except that in this embodiment, step S1 selects sodium chloride with a particle size of 100 μm, magnesium oxide with a particle size of 100 μm, and diatomaceous earth with a particle size of 100 μm. Sodium chloride, magnesium oxide, and diatomaceous earth are dried separately at a drying temperature of 150° C. and a heat preservation time of 4 hours.

[0112] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 180 MPa and a tensile strength of 23 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 90 minutes.

[0113] Example 7

[0114] This embodiment provides a water-soluble salt core.

[0115] The mass percentage components of the water-soluble salt core are the same as those in Example 1.

[0116] The method for preparing the water-soluble salt core is basically the same as that of Example 1, except that in this example, in step S3, the pressure of CO2 is 1 MPa.

[0117] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 200 MPa and a tensile strength of 25.5 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 120 minutes.

[0118] Example 8

[0119] This embodiment provides a water-soluble salt core.

[0120] The mass percentage components of the water-soluble salt core are the same as those in Example 1.

[0121] The preparation method of the water-soluble salt core is basically compared with that of Example 1, except that in this embodiment, during the pressing process in step S3, the salt core mold temperature is controlled to 120°C, the pressing pressure is 200 MPa, and the pressing time is 3 min.

[0122] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 178 MPa and a tensile strength of 24 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 95 minutes.

[0123] Example 9

[0124] This embodiment provides a water-soluble salt core.

[0125] The mass percentage components of the water-soluble salt core are the same as those in Example 1.

[0126] The preparation method of the water-soluble salt core is basically the same as that of Example 1, except that in this embodiment, during the pressing treatment in step S4, during the sintering treatment, the sintering temperature is 250° C. and the holding time is 0.5 h.

[0127] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 185 MPa and a tensile strength of 24.5 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being soaked in hot water at a temperature of 70°C to 100°C for 100 minutes.

[0128] Comparative Example 1

[0129] This comparative example provides a water-soluble salt core.

[0130] The water-soluble salt core component of this comparative example is different from that of Example 1 in that water glass is missing from the water-soluble salt core component of this comparative example. Specifically, the water-soluble salt core of this comparative example includes the following components by mass percentage: 65% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 10% polyvinyl alcohol fiber, and 10% binder. Among them, the binder is silica sol.

[0131] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0132] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 80 MPa and a tensile strength of 10 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 25 minutes.

[0133] Comparative Example 2

[0134] This comparative example provides a water-soluble salt core.

[0135] The water-soluble salt core component of this comparative example is different from that of Example 1 in that the water-soluble salt core component of this comparative example lacks a binder. Specifically, the water-soluble salt core of this comparative example includes the following components in mass percentage: 60% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 15% water glass, and 10% polyvinyl alcohol fiber, wherein the binder is silica sol.

[0136] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0137] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 95 MPa and a tensile strength of 13 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 70 minutes.

[0138] Comparative Example 3

[0139] This comparative example provides a water-soluble salt core.

[0140] The water-soluble salt core component of this comparative example is different from that of Example 1 in that the water-soluble salt core component of this comparative example lacks magnesium oxide. Specifically, the water-soluble salt core of this comparative example includes the following components in mass percentage: 55% sodium chloride, 10% diatomaceous earth, 15% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0141] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0142] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 115 MPa and a tensile strength of 13 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 90 minutes.

[0143] Comparative Example 4

[0144] This comparative example provides a water-soluble salt core.

[0145] The water-soluble salt core component of this comparative example is different from that of Example 1 in that diatomaceous earth is lacking in the water-soluble salt core component of this comparative example. Specifically, the water-soluble salt core of this comparative example includes the following components in mass percentage: 60% sodium chloride, 5% magnesium oxide, 15% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0146] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0147] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 100 MPa and a tensile strength of 11 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 80 minutes.

[0148] Comparative Example 5

[0149] This comparative example provides a water-soluble salt core.

[0150] The water-soluble salt core component of this comparative example is different from that of Example 1 in that the water-soluble salt core component of this comparative example lacks polyvinyl alcohol fiber. Specifically, the water-soluble salt core of this comparative example includes the following components in mass percentage: 60% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 15% water glass, and 10% binder, wherein the binder is silica sol.

[0151] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0152] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 115 MPa and a tensile strength of 16 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 130 minutes.

[0153] Comparative Example 6

[0154] This comparative example provides a water-soluble salt core.

[0155] The water-soluble salt core component of this comparative example is different from that of Example 1 in that the water-soluble salt core of this comparative example includes the following components in mass percentage: 53% sodium chloride, 2% magnesium oxide, 10% diatomaceous earth, 15% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0156] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0157] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 120 MPa and a tensile strength of 14 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 93 minutes.

[0158] Comparative Example 7

[0159] This comparative example provides a water-soluble salt core.

[0160] The water-soluble salt core components of this comparative example are compared with those of Example 1, except that the water-soluble salt core of this comparative example includes the following components in mass percentage: 57% sodium chloride, 5% magnesium oxide, 3% diatomaceous earth, 15% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0161] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0162] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 110 MPa and a tensile strength of 13 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 82 minutes.

[0163] Comparative Example 8

[0164] This comparative example provides a water-soluble salt core.

[0165] The water-soluble salt core components of this comparative example are compared with those of Example 1, except that the water-soluble salt core of this comparative example includes the following components in mass percentage: 62% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 3% water glass, 10% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0166] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0167] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 90 MPa and a tensile strength of 12 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 38 minutes.

[0168] Comparative Example 9

[0169] This comparative example provides a water-soluble salt core.

[0170] The water-soluble salt core component of this comparative example is different from that of Example 1 in that the water-soluble salt core of this comparative example includes the following components in mass percentage: 58% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 15% water glass, 2% polyvinyl alcohol fiber, and 10% binder, wherein the binder is silica sol.

[0171] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0172] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 120 MPa and a tensile strength of 17 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 120 minutes.

[0173] Comparative Example 10

[0174] This comparative example provides a water-soluble salt core.

[0175] The water-soluble salt core components of this comparative example are compared with those of Example 1, except that the water-soluble salt core of this comparative example includes the following components in mass percentage: 58% sodium chloride, 5% magnesium oxide, 10% diatomaceous earth, 15% water glass, 10% polyvinyl alcohol fiber, and 2% binder, wherein the binder is silica sol.

[0176] The preparation method of the water-soluble salt core is the same as that in Example 1.

[0177] The prepared water-soluble salt core was subjected to performance testing. The water-soluble salt core had a pressure tolerance of 100 MPa and a tensile strength of 14 MPa. The water-soluble salt core could be hydrolyzed and dispersed after being immersed in hot water at a temperature of 70°C to 100°C for 60 minutes.

[0178] It can be seen from Examples 1 to 9 and Comparative Examples 1 to 10 that when the content of magnesium oxide, diatomaceous earth, water glass, polyvinyl alcohol fiber or binder in the water-soluble salt core is too little or lacking, the mechanical strength and toughness of the water-soluble salt core will be affected, resulting in a lower pressure resistance of the water-soluble salt core, which is not conducive to the preparation of metal powder injection molding products. Since in the preparation process of metal powder injection molding products, the molding pressure during injection molding is 150Mpa~200Mpa, and diatomaceous earth has a porous characteristic. During the processing and pressing process of the water-soluble salt core preparation, particles such as sodium chloride and magnesium oxide are easily connected to form a large number of three-dimensional through channels, thereby improving the strength and toughness of the water-soluble salt core. If the diatomaceous earth content is reduced to less than 5% or diatomaceous earth is not included, effective three-dimensional through channels cannot be formed, thereby reducing the strength of the salt core. The composite bonding system of water glass and silica sol can significantly improve the strength and pressure resistance of the salt core. Reducing the content of water glass to less than 5% or the content of silica sol to less than 3% can accelerate the dissolution efficiency of the salt core, but the strength and pressure resistance are also significantly reduced. Polyvinyl alcohol fiber (PVA) has high strength and good affinity and binding with sodium chloride and magnesium oxide, which can improve the mechanical strength of the water-soluble salt core. At the same time, polyvinyl alcohol fiber (PVA) has good water solubility, which helps the water-soluble salt core in the preparation process of metal powder injection molding products to be de-cored by hot water. When the content of polyvinyl alcohol fiber is less than 3%, the mechanical strength of the salt core is also significantly reduced. Magnesium oxide has a high hardness and is dispersed in the salt core to improve the impact resistance of the salt core. When the content of magnesium oxide is less than 5%, the strengthening effect is poor. Therefore, the water-soluble salt core in Comparative Examples 1 to Comparative Examples 10 cannot withstand the molding pressure, and therefore, it will cause poor injection molding effect or injection molding failure in the preparation process of metal powder injection molding products, and metal powder injection molding products cannot be prepared.

[0179] In summary, the water-soluble salt core of the present application has high mechanical strength and toughness, and has good hydrolysis and disintegration properties, which is helpful for implementing the hot water core removal process when preparing metal powder injection molding products.

[0180] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0181] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0182] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A water-soluble salt core, characterized in that The composition comprises the following components in percentage by weight: 50% to 60% sodium chloride, 5% to 15% magnesium oxide, 5% to 10% diatomaceous earth, 5% to 15% water glass, 3% to 10% polyvinyl alcohol fiber and 3% to 10% binder.

2. The water-soluble salt core according to claim 1, characterized in that The invention comprises the following components in mass percentage: 50% to 60% sodium chloride, 7.5% to 12.5% ​​magnesium oxide, 5% to 8% diatomaceous earth, 5% to 12.5% ​​water glass, 3% to 7.5% polyvinyl alcohol fiber and 5% to 10% binder.

3. The water-soluble salt core according to claim 1, characterized in that The invention comprises the following components in mass percentage: 55% to 60% sodium chloride, 7.5% to 10% magnesium oxide, 7% to 7.5% diatomaceous earth, 7.5% to 12.5% ​​water glass, 5% to 7.5% polyvinyl alcohol fiber and 5% to 7.5% binder.

4. The water-soluble salt core according to any one of claims 1 to 3, characterized in that The binder includes silica sol.

5. The water-soluble salt core according to any one of claims 1 to 3, characterized in that The water-soluble salt core has a pressure tolerance of greater than 150 MPa, and can be hydrolyzed and dispersed after being soaked in hot water at a temperature of 70° C. to 100° C. for 30 min to 120 min.

6. A method for preparing a water-soluble salt core according to any one of claims 1 to 5, characterized in that: The steps include: Drying the sodium chloride, magnesium oxide and diatomaceous earth respectively; The dried sodium chloride, magnesium oxide, diatomaceous earth, water glass, polyvinyl alcohol fiber, and binder are mixed evenly according to a preset ratio to obtain a mixed material; placing the mixed material in a salt core mold and performing compression processing to obtain a compressed intermediate; as well as The pressed intermediate is sintered to obtain a water-soluble salt core.

7. The method for preparing a water-soluble salt core according to claim 6, characterized in that: During the drying process, the drying temperature is 150° C. to 200° C., and the heat preservation time is at least 3 hours.

8. The method for preparing a water-soluble salt core according to claim 6, characterized in that: During the pressing process, the temperature of the salt core mold is controlled to be 80° C. to 120° C., the pressing pressure is 200 MPa to 300 MPa, and the pressing time is 3 min to 10 min.

9. The method for preparing a water-soluble salt core according to any one of claims 6 to 8, characterized in that: During the sintering treatment, the sintering temperature is 200° C. to 250° C., and the heat preservation time is 0.5 h to 2 h.

10. The method for preparing a water-soluble salt core according to any one of claims 6 to 8, characterized in that: After the drying process, at least one of the following conditions is met: (1) Controlling the particle size of the sodium chloride to be 50 μm to 100 μm; (2) Controlling the particle size of the magnesium oxide to be 50 μm to 100 μm; (3) The particle size of the diatomaceous earth is controlled to be 50 μm to 100 μm.

11. The method for preparing a water-soluble salt core according to any one of claims 6 to 8, characterized in that: When the mixed material is placed in a salt core mold for pressing, the following step is also included: pressurized CO2 is introduced into the salt core mold, wherein the pressure of CO2 is 0.5Mpa~1Mpa.

12. A method for preparing a metal powder injection molding product, characterized in that: The steps include: Placing the water-soluble salt core according to any one of claims 1 to 5 or the water-soluble salt prepared by the preparation method according to any one of claims 6 to 11 in a mold cavity of a molding mold, wherein the gap between the water-soluble salt core and the mold cavity of the molding mold forms a molding chamber; Placing metal powder in a molding cavity between the water-soluble salt core and the molding die for injection molding; as well as The molding mold is removed, and the water-soluble salt core and the injection product are immersed in hot water at a temperature of 70° C. to 100° C. for 30 min to 120 min to achieve hydrolysis and disintegration of the water-soluble salt core to obtain a metal powder injection molding product.

13. The method for preparing a metal powder injection molding product according to claim 12, characterized in that: During injection molding, the molding pressure is 150Mpa~200Mpa; And / or, the metal powder includes one or more of stainless steel powder, low alloy steel powder, titanium alloy powder and cemented carbide powder.

14. A water outlet device housing, characterized in that: The metal powder injection molding product is prepared by the preparation method of any one of claims 12 to 13.

Citation Information

Patent Citations

  • Foundry water-soluble composite salt core material, salt core preparation method and prepared salt core

    CN101869963A

  • Easily-collapsing molding sand for aluminum alloy castings and preparing method for easily-collapsing molding sand

    CN105562584A

  • Water-soluble salt core type metal powder injection molding technology

    CN105798308A

  • Anti-adhesion precoated sand

    CN105903889A

  • Water-soluble mold core used for high-precision aluminium alloy casting and preparation method thereof

    CN105964890A